Proyectos hídricos y ecología política del desarrollo en Latinoamérica: Hacia un marco analítico - Romero, Hugo; Sasso, Jimena (European Review of Latin American and Caribbean Studies, 2014)
Hydroelectric projects and the political ecology of development in Latin America: Towards a theoretical frameworkHydroelectric projects and the political ecology of development in Latin America: Towards a theoretical framework This article analyses from political ecology the hegemonic and counter-hegemonic discourses about dams and the political-ecological dynamics in which dams are insert. To do that, the case of the HidroAysén project in Chilean Patagonia and the dam El Zapotillo in Jalisco state in Mexico are analysed. In the conclusion, both cases are compare and it is argue that the construction of dams is linked to political, class, race and spatial allocation inequalities, which generate more social, material and symbolic exclusions.ResumenEste artículo analiza desde la ecología política los discursos hegemónico y contra-hegemónico sobre represas, y las dinámicas político-ecológicas en los cuales la construcción de represas está inserta. Para ello, se analiza el caso del proyecto HidroAysén en la Patagonia Chilena, y el caso de la represa El Zapotillo en el estado de Jalisco en México. En las conclusiones se comparan ambos casos y se argumenta que la construcción de represas está vinculada a desigualdades políticas, de clase, de raza y localización espacial, generando más exclusiones sociales, materiales y simbólicas.